Epigenetic down‐regulation of SOX2 is an independent poor prognostic factor for hypopharyngeal cancers. Issue 5 (23rd January 2018) - Avincsal, Mehmet Ozgur; Jimbo, Naoe; Fujikura, Kohei; Shinomiya, Hirotaka; Otsuki, Naoki; Morimoto, Koichi; Furukawa, Tatsuya; Morita, Naruhiko; Maehara, Ritsuko; Itoh, Tomoo; Nibu, Ken‐ichi; Zen, Yoh
Abstract : Aims: We recently reported that a small subset (7%) of oesophageal squamous cell carcinomas completely lacking SOX2 expression had unique clinicopathological features and a dismal prognosis. The aim of the present study was to elucidate whether the findings obtained in oesophageal cancers are applicable to hypopharyngeal squamous cell carcinomas (HPSCCs) or oropharyngeal squamous cell carcinomas (OPSCCs). Methods and results: The study cohort consisted of consecutive patients with HPSCC ( n  = 130) and OPSCC ( n  = 65) who underwent surgery without preoperative therapy. On immunostaining, SOX2 was almost entirely negative in 10 of 130 HPSCCs (8%) and seven of 65 OPSCCs (11%). No significant differences were observed in clinicopathological features, including p16 status, between SOX2‐positive and SOX2‐negative cancers. However, patients with SOX2‐negative HPSCC had significantly worse overall and recurrence‐free survival than those with SOX2‐positive HPSCC, whereas such a prognostic relationship was not confirmed in patients with OPSCC. In a multivariate analysis, the loss of SOX2 expression appeared to be an independent poor prognostic factor for patients with HPSCC. In a sequencing analysis, no mutation was found in SOX2 . As SOX2 is known to contain an extensive CpG island before the transcription start site, methylation‐specific polymerase chain reaction for the SOX2 promoter was performed. Methylated alleles were found in nine of 10 SOX2‐negative HPSCCs but in none of SOX2‐positive HPSCCs. Conclusions: Similarly to oesophageal cancers, a small subset (8%) of HPSCCs characteristically almost completely lacking SOX2 expression appeared to be aggressive neoplasms with high recurrence rates. Promoter hypermethylation was determined to be a major mechanism underlying epigenetic SOX2 silencing.